True uterus didelphys in she-camel: a case report and review of literature - Mahdy, Mohamed A. A.; Nasr Eldeen, Mohammed S. (Frontiers in Veterinary Science, 2024)
Background: Uterus didelphys is a rare congenital anomaly of the female reproductive tract characterized by divided uterine cervix and body. It occurs due to abnormal development of the paramesonephric (Müllerian) duct. Different forms of uterus didelphys have been reported in several animal species including bovine, equine, ewe, goat, swine, and bitch. However, there is no previous report that has documented completely divided female genital tract in she-camel. Moreover, there is a lack of literature regarding this anomaly in animals. Therefore, the present study report, for the first time, a rare case of completely divided female genital tract in a she-camel. In addition reviews the existing relevant literature reporting uterus didelphys in different animal species. Case presentation: A female reproductive tract of she-camel, approximately 10 years old, with a history of previous successful pregnancy, was brought to the anatomy department following slaughtering of the animal. Initial examination revealed apparently normal reproductive tract consisted of two ovaries, two fallopian tubes, uterus, and vagina. Closer examination revealed the presence of a completely divided vagina, each part of the vagina had an external os opened into it, and a divided uterine body and cervix. Intrauterine infusion of saline through one external os confirmed complete separation of uterine body and cervix. Conclusions: To the authors' knowledge, this is the first reported case of completely divided female genital tract in a she-camel. This review summarizes the previous reports about uterus didelphys in farm animals.